Impact of Soil Drying-Rewetting Stress on Microbial Communities and Activities and on Degradation of Two Crop Protection Products - Pesaro, Manuel (American Society for Microbiology, 2004)
Prior to registration of crop protection products (CPPs) their persistence in soil has to be determined under defined conditions. For this purpose, soils are collected in the field and stored for up to 3 months prior to the tests. During storage, stresses like drying may induce changes in microbiological soil characteristics (MSCs) and thus may influence CPP degradation rates. We investigated the influence of soil storage-related stress on the resistance and resilience of different MSCs by assessing the impact of a single severe drying-rewetting cycle and by monitoring recovery from this event for 34 days. The degradation and mineralization of the fungicide metalaxyl-M and the insecticide lufenuron were delayed by factors of 1.5 to 5.4 in the dried and rewetted soil compared to the degradation and mineralization in an undisturbed reference. The microbial biomass, as estimated by direct cell counting and from the soil DNA content, decreased on average by 51 and 24%, respectively. The bulk microbial activities, as determined by measuring substrate-induced respiration and fluorescein diacetate hydrolysis, increased after rewetting and recovered completely within 6 days after reequilibration. The effects on Bacteria, Archaea, and Pseudomonas were investigated by performing PCR amplification of 16S rRNA genes and reverse-transcribed 16S rRNA, followed by restriction fragment length polymorphism (RFLP) and terminal RFLP (T-RFLP) fingerprinting. Statistical analyses of RFLP and T-RFLP profiles indicated that specific groups in the microbial community were sensitive to the stress. In addition, evaluation of rRNA genes and rRNA as markers for monitoring the stress responses of microbial communities revealed overall similar sensitivities. We concluded that various structural and functional MSCs were not resistant to drying-rewetting stress and that resilience depended strongly on the parameter investigated.